Examining the South China Sea Dispute with General Morphological Analysis [version 2; peer review: 2 approved] - Zachary Lavengood (Stosunki Międzynarodowe, 2023)
The South China Sea dispute is among the most volatile flashpoints in contemporary international relations. This study examines this dispute using the general morphological analysis (GMA) methodology employing eight factors of analysis. These produced 65,536 distinct outcomes in a cross-consistency matrix (CCM) which exist on a spectrum of plausibility. Three scenarios were chosen for foresight analysis which project contemporary trends into the near-to-mid-term future. After the analysis of hundreds of different combinations from the CCM which remained after auditing for analytical noise and plausibility this research found that much of the foresight produced scenarios which were similar to a ‘dispute stagnation’ scenario. This highlights the present realities of the dispute wherein all parties have entrenched into their political and physical positions with little alternative outside of direct confrontation, an outcome which though possible, is unappealing to claimants due to the secondary effects which it would bring.